Physical Acceptability Of The Renyi Holographic Dark Energy Model UnderThe Hubble's Cutoff In ƒ (T, B) Gravity - Katre, N. T.; Pawar, Kalpana; Dabre, A. K.
The paper deals with the investigations of the behaviour and physical acceptability of the spatially homogeneous and isotropic FLRW space-time filled with pressureless matter and Rényi holographic dark energy under the Hubble's IR-cutoff in the framework of ƒ(T, B) gravity. We have calculated some cosmological parameters to study the astrophysical consequences of the constructed model. We discussed their behaviour during the cosmic evolution, in particular, the statefinder and EoS parameters. It is found that the constructed Rényi holographic dark energy model travels from Phantom, ɅCDM , and lastly enters & remains in Quintessence dark energy era with the increase in redshift. Статья посвящена исследованию поведения и физической приемлемости пространственно однородного и изотропного пространства- времени FLRW, заполненного материей без давления и голографической темной энергией Реньи при ИК-пороге Хаббла в рамках гравитации ƒ(T, B). Рассчитаны некоторые космологические параметры для изучения астрофизических следствий построенной модели. Обсуждается их поведение в ходе эволюции, в том числе, параметры определителя состояния и параметры EoS. Обнаружено, что построенная голографическая модель темной энергии Реньи "путешествует" из Фантома, ɅCDM и, наконец, входит и остается в эре темной энергии Квинтэссенции с увеличением красного смещения.
Keywords: Astrophysics